Hábitos de estudio y habilidades investigativas en estudiantes de la carrera profesional de Ciencias Sociales y desarrollo rural en una Universidad Nacional - Poma Ccora, Deysi Melisa (2023)
The aim of the research was to determine the relationship between study habits and research skills in students pursuing the professional career of Social Sciences and Rural Development at a national university. The scientific method was used as the general approach, specifically employing a descriptive design correlational research. Questionnaires and a knowledge test were administered to a sample of 70 students as instruments. The research presents statistical results from the conducted survey, along with subsequent data processing, highlighting the association between study habits and research skills. Students suggest that success in the field of research is attainable, as study habits contribute to the development of essential skills in the research process.